Clinical outcome of non-alcoholic fatty liver disease: an 11-year follow-up study - Steven Dooley; Juan Du; Xiaoping Tang; Lan Chen; Jinzhu Jia; Fujun Li; Yanyan Shi; Christoph Meyer; Zhongwei Zhu; Yanming Zhang; Roman Liebe; Keming Hu; et al. (BMJ Open)
Objectives To clarify non-alcoholic fatty liver disease (NAFLD) prevalence, risk factors and clinical outcome in an exemplary Chinese population, a cohort of company employees was followed up for 11 years.Design Retrospective cohort study.Setting Between 2006 and 2016 in Ning bo, China.Participants 13 032 company employees.Results Over 11 years, the prevalence of NAFLD increased from 17.2% to 32.4% (men 20.5%–37% vs women 9.8%–22.2%). Male peak prevalence was between 40 and 60 years of age, whereas highest prevalence in women was at an age of 60 years and older. Logistic and Cox regression revealed 16 risk factors, including body mass index (BMI), albumin, white blood cell, triglycerides (TG), high-density lipoprotein, glutamyl transpeptidase, alanine transaminase, creatinine, urea acid, glucose, systolic blood pressure, diastolic blood pressure, blood sedimentation, haemoglobin, platelet and apolipoprotein B2 (p<0.05 for all factors). The area under the curve of these variables for NAFLD is 0.88. However, cause-effect analyses showed that only BMI, gender and TG directly contributed to NAFLD development. Over an 11-year follow-up period, 12.6%, 37.7% and 14.2% of male patients with NAFLD and 11.6%, 44.7% and 22.6% of female patients with NAFLD developed diabetes, hypertension and hyperuricaemia, respectively. Except one male patient who developed cirrhosis, no patients with NAFLD progressed into severe liver disease.Conclusion Diabetes, hypertension and hyperuricaemia are the main clinical outcomes of NAFLD. Eleven years of NAFLD are not sufficient to cause severe liver disease. Age and obesity are direct risk factors for NAFLD. BMI, gender and TG are three parameters directly reflecting the occurrence of NAFLD.